The dynamic metabolomic changes throughout mouse epididymal lumen fluid potentially contribute to sperm maturation. (1st December 2017) - Hu, S.‐G.; Liang, A.‐J.; Yao, G.‐X.; Li, X.‐Q.; Zou, M.; Liu, J.‐W.; Sun, Y.
Summary: Epididymal lumen fluids are directly responsible for sperm maturation. However, very little is known about the molecular details of small molecule metabolites in the epididymal lumen fluids until now. Here we identified and compared the metabolic profiles of mouse caput and cauda epididymal lumen fluids using GC‐MS technique. Among 236 metabolites identified in caput and cauda epididymis, 36 were significantly enriched in caput epididymis while 18 were significantly enriched in cauda epididymis. Pathway analysis identified ascorbate and aldarate metabolism and beta‐alanine metabolism as most relevant pathways in caput and cauda epididymis, respectively. Ascorbate, dehydroascorbic acid and beta‐alanine associated with these two pathways were firstly reported in mouse epididymal lumen fluids and might play important roles in sperm maturation.